2020
DOI: 10.7759/cureus.10147
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Medical Students During the Coronavirus Disease 2019 Pandemic: A Cross-Sectional Survey Study

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic affects the education of medical students around the world and countries have had differing responses in dealing with this dynamic situation. The role of medical students in fighting this pandemic is controversial and it is yet to be elucidated how they can best be of service. The aim of this study is to evaluate the working fields of volunteering students and the impact of the pandemic on final year students from a student's perspective. Methods: An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
3
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 20 publications
5
51
3
5
Order By: Relevance
“…However, this was not accompanied by a proportional number of participants with adequate readiness to practice, indicating that further preparations are required to ensure that they are equipped with sufficient knowledge and aptitude [ 9 ]. This is in accordance to the findings of previous studies in Ireland [ 24 ] and Germany [ 5 ] which reported high rates of willingness to volunteer among medical students [ 5 , 24 ] with relatively low rates of readiness to practice [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, this was not accompanied by a proportional number of participants with adequate readiness to practice, indicating that further preparations are required to ensure that they are equipped with sufficient knowledge and aptitude [ 9 ]. This is in accordance to the findings of previous studies in Ireland [ 24 ] and Germany [ 5 ] which reported high rates of willingness to volunteer among medical students [ 5 , 24 ] with relatively low rates of readiness to practice [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…In fact, several studies had consistently reported that medical students were concerned about approaching patients infected with unknown diseases. In such cases, it may be plausible to focus the allocation of these volunteering students to activities relating to early levels of prevention with minimum risk of exposure, including health education and promotion, contact tracing and triages, as well as peer supports for isolating patients and HCWs [ 5 , 36 , 37 ]. Contrarily, volunteering opportunity in clinical settings should be strictly limited to clinical-year students, provided that they are well-prepared and protected [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These HCPs have to do this job under new working conditions, both due to the physical work environment in newly created COVID-19 departments as well as professionally depending on their previous knowledge, skills and experiences. While research has described how HCPs during the rst phase of the COVID-19 pandemic approached their obligations with a stoic and altruistic orientation towards their work (15), others have reported how questions of who will step up to the plate in this ongoing crisis arise (16).…”
Section: Introductionmentioning
confidence: 99%